Hematopoietic Stem Cell Protocols - Bunting, Kevin D.; Bunting, Kevin D. (Methods in Molecular Biology,, 2008)
With new technologies emerging and old technologies being reimagined, the field of hematopoietic stem cell (HSC) research continues to grow rapidly in pursuit of improved therapies for many blood diseases. Updating and building upon the thorough first edition's foundation, Hematopoietic Stem Cell Protocols, Second Edition provides up-to-date protocols developed in the HSC field. A team of leading researchers supply this volume with in-depth, readily reproducible methods for effective characterization of HSC and their developmental potential. An introductory chapter also hints at potential techniques that may develop in the future. Following the format of the successful Methods in Molecular Biology™ series, each protocol offers step-by-step laboratory instructions, lists of the necessary equipment, and tips on troubleshooting and avoiding known pitfalls. Essential for the laboratory-based researcher, Hematopoietic Stem Cell Protocols, Second Edition is a much needed technical resource in the critically important field of stem cell investigation.